Feasibility of laparoscopic repair of peptic ulcer perforation - Sisodiya, Sanjay; Patel, Badri Prasad (International Surgery Journal, 2021)
Background: Perforation is a common complication of peptic ulcer disease and presents as Perforation peritonitis. It has the highest number of mortality among all complications (≈15%). In spite of modern progress in the management, it is still a life-threatening catastrophe. Emergency surgery for complicated cases required in 7% of hospitalized peptic ulcer disease patients. Factors such as >24 hours of history, concomitant disease, shock, post operated wound infections, all are associated with increase in mortality and morbidity. Methods: A Prospective, observational, single hospital base study done during the period from 2016 to 2020 in the Department of Surgery, Gandhi medical college Bhopal. Sample size was taken 63 Results: 52 out 63 cases presented with perforation peritonitis included under study period, 11 cases were excluded due to death and absconding of cases. In rest 52 cases, 15 of them went through laparoscopic repair, 28.85% of the cases were shifted directly to ORG. Conclusions: Laparoscopic repair of peptic ulcer perforation is feasible if patient presents early to the hospital. All perforation peritonitis should give fair chance to repair laparoscopically if patient’s general condition and anesthetic permits. This is a good alternative for conventional open surgery with less post-operative pain, early return to normal activities, less hospital stays and few postoperative wound infections. Thus it can significantly decrease the economic burden.